Landscape‐scale modelling of erosion processes and soil carbon dynamics under land‐use and climate change in agroecosystems. (27th May 2015) - Lacoste, M.; Viaud, V.; Michot, D.; Walter, C.
Summary Soil organic carbon (SOC) sequestration and soil redistribution are linked to soil properties, land use, farming system and climate. In a global‐change context, landscape and climate changes are expected and will most probably have impacts on changes in the soil. Soil change was simulated from 2010 to 2100 in an 86‐ha hedgerow landscape under different scenarios of landscape and climate changes. These scenarios combined contrasting land uses, hedgerow networks and climates. Two models were combined to evaluate the impact of these scenarios on soils: LandSoil, a soil redistribution model, and a SOC model based on RothC‐26.3. A soil thickness of 105 cm was considered. The results indicate that the main factor influencing soil degradation was land‐use change: when compared with the baseline business‐as‐usual landscape, the landscape with the most intensive agricultural systems had the greatest soil erosion (+0.26 t ha−1 year−1) and reduced mean SOC stocks (−17 t ha−1 after 90 years). The second significant factor was climate change, followed by hedgerow network density. Sensitivity to climate change differed between landscapes, and the most sensitive were those with continuous winter wheat. The results indicate that a hedgerow landscape is well adapted to protect soil (regarding carbon storage and soil erosion) in a context of climate change. However, this type of landscape is highly sensitive to cropping intensification and should be protected.